On the Issue of Choosing the Optimal Material Management System in the Enterprise (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article the problem of the choice of material management in domestic enterprises. Landing and grounded nature of the logistics process. Particular attention is paid to organization subsystems logistics material management that are used by domestic enterprises
Keywords: logistics, logistics management, logistics system, the material flows